Polymorphism in crystals of bis(4-bromophenyl)fumaronitrile through vapour phase growth. Issue 48 (17th October 2017) - Jensen, Torsten T.; Potticary, Jason; Terry, Lui R.; Bruce Macdonald, Hannah E.; Brandenburg, Jan Gerit; Hall, Simon R.
Abstract : We have linked polymorphic selectivity of crystals of bis(4-bromophenyl)fumaronitrile grown via physical vapour transport and their fluorescence to the lattice properties of each polymorph. Abstract : Polymorphic selectivity within crystals grown via physical vapour transport (PVT) is dependent on the thermodynamic stabilities of differing molecular conformations and the kinetic regime within the growth apparatus. Crystals of bis(4-bromophenyl)fumaronitrile have been grown for the first time via this method, with the formation of both the conventional polymorph and a new, unforseen polymorph. Analysis suggests that the conventional form is less thermodynamically stable, with this form crystallising at higher temperature than the newly discovered form due to the release of binding energy of intermolecular interactions during the growth process. Fluorometry reveals the new form to exhibit weaker, red-shifted fluorescence emission owing to greater intermolecular π–π overlap.